A study on abuse of topical corticosteroids in patients who attended dermatology venerology leprosy outpatient department - Sarathi, R.; Christypriya, A.; Kaviarasan, P. K.; Mohanta, Guru Prasad (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Topical corticosteroids (TCs) are widely used in the patients affected with dermatoses. Abuse of these agents may cause severe adverse effects. Aim of the study was to study the abuse of TCs in patient who attend Dermatology, Venereology, and Leprosy (DVL) outpatient department. Methods: This prospective observational study was conducted in department of DVL at Rajah Muthiah Medical college, Tamil Nadu during the period of six months from November 2018 to April 2019. The patients were enrolled for the study based on inclusion and exclusion criteria. Results: Totally 50 patients with adverse drug reactions (ADRs) by the abuse of TCs were enrolled for the study. It was found that TCs were abused in all ages and equally in both genders. Nearly 72% of the people used TCs for Tinea infection and 20% of the people used TCs for acne vulgaris. Very high potent TCs such as betamethasone and beclomethasone were abused by 55% of the patient. Tinea incognito (TI) was found as common ADRs by the abuse of TCs (74%). Nearly 88% of the people bought TCs from pharmacies without prescription. Sixteen brands were found as easily accessible and affordable for the patients. Medication adherence were increased by 60% after the patient counselling. Conclusion: This study concludes, TI was found as a common ADR in patients who abused TCs such as betamethasone, beclomethasone and clobetasol. High potent TCs should not be allowed to dispense without prescription. Withdrawal of TCs will reduce the risk of ADRs.